Medicines can affect thermoregulation and accentuate the risk of dehydration and heat‐related illness during hot weather. (13th June 2015) - Westaway, K.; Frank, O.; Husband, A.; McClure, A.; Shute, R.; Edwards, S.; Curtis, J.; Rowett, D.
Summary What is Known and objective Hot days are increasingly common and are often associated with increased morbidity and mortality, especially in the elderly. Most heat‐related illness and heat‐related deaths are preventable. Comment Medicines may accentuate the risk of dehydration and heat‐related illness, especially in elderly people taking multiple medicines, through the following mechanisms: diuresis and electrolyte imbalance, sedation and cognitive impairment, changed thermoregulation, reduced thirst recognition, reduced sweat production, and hypotension and reduced cardiac output. What is new and conclusion Commonly used medicines that may significantly increase the risk include diuretics, especially when combined with an angiotensin converting enzyme (ACE) inhibitor or an angiotensin II receptor blocker (ARB), anticholinergics and psychotropics. Initiation of individualized preventive measures prior to the start of the hot weather season, which includes a review of the patient and their medicines to identify thermoregulatory issues, may reduce the risk of heat‐related illness or death.